The role of probiotics and synbiotics on treatment of gestational diabetes: systematic review and meta-analysisAJOG Global Reports at a Glance - Arresta Vitasatria Suastika, MD; I Gde Raka Widiana, PhD, MD; Ni Nengah Dwi Fatmawati, PhD, MD; Ketut Suastika, PhD, MD; Ivana Beatrice Paulus, MD; I Nengah Sujaya, PhD, M AgrSc, B.Eng (Elsevier, 2024)
OBJECTIVE: This review investigated the efficacy of probiotics and/or synbiotics in gestational diabetes mellitus treatment by targeting insulin resistance, lipid metabolism, and anti-inflammatory effects in an updated trial. DATA SOURCES: The literature review was performed using the key words "Probiotics," "Synbiotics," and "Gestational Diabetes" in several databases, including PubMed, ScienceDirect, and the Cochrane Central Register of Controlled Trials. STUDY ELIGIBILITY CRITERIA: Eligible publication was screened independently by 2 reviewers. Studies included provided at least 1 of the following outcomes: (1) blood glucose marker, including fasting blood glucose level, fasting serum insulin level, and homeostasis model assessment insulin resistance; (2) blood lipid profiles, including triglycerides, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol; and (3) nitric oxide and C-reactive protein. METHODS: All studies were reviewed using the critical appraisal Cochrane risk-of-bias tool for randomized trials. The descriptions of the extracted data were guided by the Preferred Reporting Items for Systematic Reviews 2020 statement with the Grading of Recommendations Assessment, Development, and Evaluation approach. This study was registered on the International Prospective Register of Systematic Reviews database (identification number: CRD42022375665). RESULTS: From 13 randomized controlled trials involving 896 patients, individuals with probiotic had significant reduction on homeostasis model assessment insulin resistance (mean difference, −0.72; 95% confidence interval, −1.07 to −0.38; I2, 96%; P=.00), fasting blood glucose level (mean difference, −3.79; 95% confidence interval, −6.24 to −1.34; I2, 93%; P=.00), and insulin level (mean difference, −2.43 mg/dL; 95% confidence interval, −3.37 to −1.48; I2, 54%; P=.00). Meanwhile for profile lipid, significant reduction of the mean difference was observed in the triglyceride (mean difference, −17.73 mg/dL; 95% confidence interval, −29.55 to − 5.9; P=.003) and C-reactive protein (mean difference, −1.93 dL; 95% confidence interval, −2.3 to −1.56; P=.00). CONCLUSION: Probiotic and synbiotic supplementations reduced the risk of insulin resistance and improved glycemic control, blood lipid profiles, and inflammation in women with gestational diabetes mellitus. Probiotics may be a viable option for gestational diabetes mellitus treatment; however, large-scale, well-designed randomized controlled trials with longer follow-up periods are required before they can be recommended to patients.